Plany migracyjne młodzieży z obszaru funkcjonalnego miasta Zielona Góra = Migration plans of youth from the functional area of the city of Zielona Góra - Lisowski, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article attempts to determine the scale of the potential for migration, defined as the willingness/readiness to leave the studied area, of students in their penultimate year of secondary education. The author presents survey research conducted in schools located in the Zielona Góra - Nowa Sól Functional Area (Zielona Góra, Nowa Sól, Sulechów). The empirical findings show a high willingness of students to travel outside the study area. The factor that most strongly determines the willingness to migrate is the type of school (high school students are more likely to have migration plans). Migration plans are not influenced by the town of education, which is symptomatic and shows that the different potential of the surveyed cities (above all Zielona Góra) is anyway insufficient to retain a large proportion of those wishing to migrate.
Keywords: migracje; młodzież; potencjał migracyjny; obszar funkcjonalny; migration; youth; migration potential; functional area